(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The aim of this study was to determine the best form and concentration of yogurt probiotics that can reduce leucocyte, neutrophil, lymphocyte, alkaline phosphatase, and cholesterol levels to normal limits. Materials and Methods: There were 35 Isa Brown laying hens aged 40 weeks with health conditions chosen as the object of research. We used a completely randomized design method with seven treatments. Treatments included P0: basal feed; T1: basal feed and probiotic liquid 2%; T2: basal feed and probiotic liquid 3%; T3: basal feed and probiotic liquid 4%; T4: basal feed and probiotic powder 2%; T5: basal feed and probiotic powder 3%; and T6: basal feed and probiotic powder 4%. On day 35 of the research, we collected blood samples. We analyzed the data using analysis of variance, followed by Duncan’s multiple range test. Results: This showed that probiotic liquid and powdered yogurt had a significant effect (p < 0.05) on all parameters. Supplementation with 4% probiotic powder reduced neutrophil (53.96%), lymphocyte (27.84%), and N/L ratios (36.25%); alkaline phosphatase levels (53.6%); and cholesterol levels (ApB 26.65% and LDL 42.4%) compared to the control. Conclusion: This study shows that all probiotic supplementation shows improvement in the studied parameters, but the addition of 4% probiotic powder had the best result for reducing neutrophil, lymphocyte, N/L ratio, alkaline phosphatase, and cholesterol levels compared to the control and probiotic liquid. J. Adv. Vet. Anim. Res., 11(4): 936–943, December 2024 http://doi.org/10.5455/javar.2024.k843